Risk factors of oropharyngeal carriage of Pseudomonas aeruginosa among patients from a Medical-Surgical Intensive Care Unit - Fortaleza, Carlos Magno Castelo Branco [UNESP]; Figueiredo, Ligia Castellon; Beraldo, Carolina Contador; de Melo, Edson Carvalho; Sales Pola, Patricia Maria; Nagem Aragao, Valeria Drummond (Contexto, 2009)
Oropharyngeal carriage of Pseudomonas aeruginosa is associated with increased risk of infection and may provide a source for spread of drug-resistant strains. In order to assess the incidence and risk factors of oropharyngeal carriage, we conducted a retrospective cohort study based on results of surveillance cultures (oropharyngeal swabs) from a medical-surgical intensive care unit, collected from March 2005 through May 2006. Variables investigated included demographic characteristics, comorbid conditions, invasive procedures, use of devices and use of antimicrobials. Thirty case patients with P. aeruginosa carriage were identified. Other 84 patients with surveillance cultures negative to P. aeruginosa were enrolled as control subjects. Case patients were more likely to have a solid malignancy (Odds Ratio [OR] = 12.04, 95% Confidence Interval [CI] = 1.93-75.09, p=0.008), Acquired Immunodeficiency Syndrome (AIDS, OR = 7.09, 95% CI=1.11-45.39, p = 0.04), central nervous system disease (OR = 4.51, 95% CI = 1.52-13.39, p = 0.007), or to have a central venous catheter placed (OR = 7.76, 95% CI = 1.68-35.79, p=0.009). The use of quinolones was a protective factor (OR = 0.13, 95% CI = 0.03-0.47, p = 0.002). The predominance of comorbidities as risk factors points out a group of patients to whom preventive measures should be directed.
Keywords: Pseudomonas aeruginosa; colonization; oropharyngeal carriage; surveillance cultures; intensive care unit